THREAT MODELS AND RISK ASSESSMENT FOR AUTONOMOUS TELECOM SYSTEMS OF THE FUTURE (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article analyzes existing and prospective threat models for autonomous telecom systems, classifies assets and critical risk areas, and discusses applicable risk assessment methodologies (NIST RMF, ISO/EBIOS). An integrated risk management approach is proposed, including multi-layered threat modeling, resilience assessment of AI components, and continuous security monitoring. Recommendations for telecom operators and regulators aimed at improving the security of future 5G/6G networks are formulated.